Serious health-related suffering experienced by children with disability and their families living in Bangladesh: A scoping review. (April 2023) - Smith, Suzanne E; Chowdhury, Mostofa Kamal; Doherty, Megan; Morgan, Deidre D
Background: In 2020, the International Association for Hospice and Palliative Care redefined palliative care to incorporate the concept of serious health-related suffering. An estimated 21 million children globally live with conditions which would benefit from a palliative approach to relieve suffering. Bangladesh is a lower-middle income country with isolated provision of palliative care. Aim: To synthesise existing evidence describing serious health-related suffering of children with disability and their families living in Bangladesh and the intersection between this suffering, palliative care and rehabilitation. Design: Scoping review methodology. Data sources: A search strategy related to serious health-related suffering and childhood disability was applied to online databases and grey literature. English language studies (1990–2021) were included. Papers pertaining to serious health-related suffering of typically developing children and those over eighteen years were excluded. Data which addressed the three domains of serious health-related suffering (physical, social and emotional/spiritual) were extracted. Palliative care interventions were assessed with a pre-existing checklist. Results: Forty-six studies were included, representing ten different methodologies. Sample sizes ranged from 11 to 2582 participants, with 87% of studies including children with cerebral palsy. Serious health-related suffering was described in 100% of the studies, only 14 of the studies described specific interventions to mitigate suffering. Convergence between palliative care and rehabilitation approaches was evident. Conclusion: Findings document the extensive nature and burden of serious childhood health-related suffering that may be remediated by a palliative approach. They highlight the urgent need to prioritise service development and research in this area.